Impact of the modified bleomycin, etoposide and cisplatinum chemotherapy regimen on the outcome of testicular germ cell tumor: a tertiary care institute experience - Madan, Renu; Thakur, Niketa; Rana, Sakshi; Kumar, Narendra; Yadav, Budhi Singh; Khosla, Divya; Kapoor, Rakesh (International Surgery Journal, 2019)
Background: Bleomycin, cisplatin and etoposide (BEP) based combination chemotherapy is established as standard treatment for testicular germ cell tumors. As these tumors are highly curable, so management is crucial in terms of long-term toxicity particularly lung toxicity. With standard BEP there is increased toxicity which leads to poor compliance. So, we at a tertiary care center assessed modified BEP regimen in such patients and evaluated its effectiveness in terms of response and toxicity as compared to standard BEP. Methods: Forty-nine patients of testicular germ cell tumors were enrolled in this study from January 2012 to December 2016. The modified BEP regimen consisted of bleomycin 30 IU day 1, cisplatin 20 mg/m2 day 1-5 and etoposide 100 mg/m2 day 1 to 5, given every three weeks. The planned drug intensities were 33.3 mg/m2/week for cisplatin, 166.7 mg/m2 week for etoposide and 10 IU/body/week for bleomycin. The schedule for chemotherapy was as follows: four courses of modified BEP for stage I patients and six courses of modified BEP for stage I S, II and III patients. Results: Overall response rate in our study was seen to be 81.2% which was comparable with the available evidence. Five (10.4%) patients developed febrile neutropenia. Two (4.1%) patients showed clinically evident bleomycin induced pulmonary toxicity. Lower toxicity seen in these patients led to better overall compliance. Conclusions: Modified BEP protocol is a good alternative to standard BEP with comparable efficacy and reduced toxicity.